Campylobacter jejuni colonization and population structure in urban populations of ducks and starlings in New Zealand. Issue 4 (22nd July 2013) - Mohan, Vathsala; Stevenson, Mark; Marshall, Jonathan; Fearnhead, Paul; Holland, Barbara R.; Hotter, Grant; French, Nigel P.
Abstract: A repeated cross‐sectional study was conducted to determine the prevalence of Campylobacter spp. and the population structure of C. jejuni in European starlings and ducks cohabiting multiple public access sites in an urban area of New Zealand. The country's geographical isolation and relatively recent history of introduction of wild bird species, including the European starling and mallard duck, create an ideal setting to explore the impact of geographical separation on the population biology of C. jejuni, as well as potential public health implications. A total of 716 starling and 720 duck fecal samples were collected and screened for C. jejuni over a 12 month period. This study combined molecular genotyping, population genetics and epidemiological modeling and revealed: (i) higher Campylobacter spp. isolation in starlings (46%) compared with ducks (30%), but similar isolation of C. jejuni in ducks (23%) and starlings (21%), (ii) significant associations between the isolation of Campylobacter spp. and host species, sampling location and time of year using logistic regression, (iii) evidence of population differentiation, as indicated by F ST, and host‐genotype association with clonal complexes CC ST‐177 and CC ST‐682 associated with starlings, and clonal complexes CC ST‐1034, CC ST‐692, and CC ST‐1332 associated with ducks, and (iv) greater genetic diversity and genotype richness in ducks compared with starlings. These findings provide evidence that host‐associated genotypes, such as the starling‐associated ST‐177 and ST‐682, represent lineages that were introduced with the host species in the 19th century. The isolation of sequence types associated with human disease in New Zealand indicate that wild ducks and starlings need to be considered as a potential public health risk, particularly in urban areas. Abstract : We applied molecular epidemiology and population genetics to obtain insights in to the population structure, host‐species relationships, gene flow and evolution of Campylobacter jejuni in urban ducks and starlings.